2004
DOI: 10.1192/bjp.185.5.410
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to the challenge of psychosis: personal resilience and the use of sealing-over (avoidant) coping strategies

Abstract: Sealing over was associated with multiple signs of low personal resilience in adapting to psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
141
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 29 publications
7
141
1
1
Order By: Relevance
“…Both attachment-anxiety and attachment-avoidance were significantly higher in those patients with borderline personality disorder and a history of childhood trauma, which in turn correlated with more severe clinical symptoms and interpersonal problems in adulthood (Minzenberg et al 2006). There is also evidence that childhood trauma is associated with higher rates of insecure attachment in adulthood among patients with psychosis (Tait et al 2004;Berry et al 2009). Compared with patients with secure attachments, insecure attachment has been associated with worse psychiatric symptoms (Gumley et al 2014) and social cognitive performance (Pos et al 2014).…”
Section: Attachmentmentioning
confidence: 77%
See 1 more Smart Citation
“…Both attachment-anxiety and attachment-avoidance were significantly higher in those patients with borderline personality disorder and a history of childhood trauma, which in turn correlated with more severe clinical symptoms and interpersonal problems in adulthood (Minzenberg et al 2006). There is also evidence that childhood trauma is associated with higher rates of insecure attachment in adulthood among patients with psychosis (Tait et al 2004;Berry et al 2009). Compared with patients with secure attachments, insecure attachment has been associated with worse psychiatric symptoms (Gumley et al 2014) and social cognitive performance (Pos et al 2014).…”
Section: Attachmentmentioning
confidence: 77%
“…Compared with patients with secure attachments, insecure attachment has been associated with worse psychiatric symptoms (Gumley et al 2014) and social cognitive performance (Pos et al 2014). It has also been associated with poorer engagement with clinical services and more interpersonal problems (Gumley et al 2014), including poorer treatment adherence and greater likelihood of disengagement from mental health services (Tait et al 2004;MacBeth et al 2011). These may all be important factors that contribute to the association between childhood trauma and poor functioning in these patient groups.…”
Section: Attachmentmentioning
confidence: 99%
“…Studies which have explored parental bonding experiences using the PBI within a psychosis population found higher rates of poor parental bonding as shown by the 'affectionless control' category, when compared with non-clinical controls (Onstad et al 1994;Winther Helgeland & Torgersen, 1997;Willinger et al 2002). Significant associations have also been found between the 'affectionless control' category and an earlier stage of initial hospitalisation, higher relapse rates (Parker et al 1982;Baker et al 1984;Parker & Mater, 1986) and poorer engagement with services (Tait et al 2004). There are few published studies in BD populations: Joyce (1984) found higher rates of 'affectionless control' parenting style amongst females with BD and an association with an increase in hospital admissions.…”
Section: Introductionmentioning
confidence: 82%
“…Research has shown that the presence of insecure attachment styles, particularly in patients with psychosis, is associated with increased psychotic symptomatology (Ponizovsky, Nechamkin, & Rosea, 2007), poorer engagement with treatment , less engagement with services (Tait, Birchwood & Trower, 2004); and less satisfaction with services (Rossberg, Melle, Opjordsmoen & Friis, 2006).…”
Section: Panas Directionsmentioning
confidence: 99%